Covid Conversations 5: Robert Wilson. (February 2022) - Wilson, Robert; Shevtsova, Maria
Abstract : World-renowned for having made a totally new kind of theatre, director-designer Robert Wilson first astonished international audiences in Paris in 1971 with Le Regard du sourd ( Deafman Glance ) and then with his twenty-four-hour Ouverture at the first edition of the Festival d'Automne in 1972. He also refers in this Conversation to Einstein on the Beach, premiered at the Avignon Festival in 1976, as another example among more of France offering him a home before he eventually founded the Watermill Center in 1992 on Long Island in the State of New York. Watermill, a laboratory for multidisciplinary creativity, opened its doors to the public in 2006 and is a focal point of the Conversation as a whole. Wilson's immediately pre-Covid-pandemic production of The Messiah by Mozart was premiered at the Mozartwoche Salzburg in February 2020 and performed subsequently in Paris during a brief Covid 'lull' in September of that year. Discussion of this pivotal work leads to reflections on the opera productions that he had staged not so long before it, emphasizing the elements fundamental to his compositions – light, time, space, architecture, and silence. The Conversation, followed by audience questions addressed to Wilson, took place live online and on Facebook on 4 December 2020 as a prelude to the Festival Internacional Santiago a Mil in Chile, which opened on 3 January 2021. This was the Festival's twenty-eighth year, but in a significantly restricted form due to Covid-19. A sequel to the Santiago interchange, also online but this time located in Paris, occurred on 17 September 2021. It resumes dialogue mainly on the Watermill Center's broader cultural and social goals in the present and for the future, noting as well Wilson's then current activities in Paris: a heavy schedule of four productions from the beginning of September to the end of December 2021, and a sound installation planned for 2022. Maria Shevtsova gratefully thanks the Fundación Teatro a Mil and its General Director Carmen Romero for their initiative in inviting Robert Wilson with her to converse publicly as part of the Festival a Mil, and for permission to edit the transcript for publication in New Theatre Quarterly. Thanks are due to interpreters Margit Schmohl and Jorge Ramirez, and to Maria Luisa Vergara for organizing the audience participation included below, as well as to Alfonso Arenas, former Coordinator of the Education and Communities Area at the Theatre Foundation a Mil. Warmest gratitude is extended to Robert Wilson for his generosity in all sorts of ways, and not least for finding the time to continue the Conversation in Paris. Thanks for their kind support to Nuria Moreno, Production at Teatro Real Madrid, Christof Belka, Executive Director of RW Work Ltd, Clifford Allen, Director of Archives of the Watermill Center, and Leesa Kelly and Noah Khoshbin, curators of the 2021 outdoor exhibition Minneapolis Protest Murals at the Crossroads Summer Festival held at the Watermill Center. The exhibition presented 190 public artworks from the 900 boards of the Minneapolis Protest Murals which were created organically in Minneapolis following the murder of George Floyd on 25 May 2020. Special thanks for their gift of images are given to photographers Lucie Jansch, Javier del Real, Kristian Kruuser and Kaupo Kikkas, Lovik Delger Ostenrik, and Martyna Szczesna. Kunsang Kelden and Maria Shevtsova transcribed this Conversation in two parts. Shevtsova, Editor of New Theatre Quarterly and author of Robert Wilson (Routledge, 2007; updated edition, 2019) edited and annotated the combined transcript for publication.